Análise do perfil de proteínas salivares, experiência de cárie, nível de Streptococcus mutans em população de crianças desnutridas - Mota, Ana Catarina de Miranda (2008)
The aim of the present study was to compare caries experience (dmfs), severity of early childhood caries (S-ECC), salivary mutans streptococci (MS) levels, total protein concentration (TPC) and salivary protein profi le (SPP) between nourished and malnourished children. One hundred and twenty 12-70 month-old malnourished children, with and without ECC were separated into being mildly (GI, n=31), moderately (GII, n=59) or severely (GIII, n=31) malnourished, according to WHO standards. Forty-seven nourished children (GN) were used as controls. Unstimulated whole saliva was collected from all participants, subsequently centrifuged. Supernatants were lyophilized and stored at -20o C for posterior TPC analysis by the Bradford method. Salivary protein profi le was obtained by electrophoresis in SDSpoliacrilamide gel through the Laemmli method. Stimulated whole saliva was collected and used for MS detection in MSB agar medium. MS concentration in saliva was reported in cfu/ mL. Dental examination was performed and dmfs scores and S-ECC were calculated. Age (p=0,0000), MS counts (p=0,0321) and nutritional status (p=0,0316) demonstrated positive contribution for the development of dental caries. However, gender (p=0,7094) and TPC (0,2720) did not signifi cantly contribute with caries experience. When compared to GN, children in GI (p=0,0042) and GIII (p=0,0372) presented higher risk of experiencing dental caries. In addition, no differences in SPP were observed between these groups. GIII children did not express one protein band (123,56+4,35 kDa) in the presence of dental caries. TPC was not associated with caries experience (p=0,5651), severity of ECC (p=0,6015) or MS counts (p=0,2162). Our results suggest that nutritional status increases caries risk in mildly and severely malnourished children, and salivary protein profi le differs among severely malnourished children with dental caries.